The Present State of Scholarship in the History of Rhetoric : A Twenty-First Century Guide - Horner, Winifred Bryan; Gaillet, Lynee Lewis (Book collections on Project MUSE., 2010)
"Through two previous editions, The Present State of Scholarship in Historical and Contemporary Rhetoric has not only introduced new scholars to interdisciplinary research but also become a standard research tool in a number of fields and pointed the way toward future study." "Adopting research methodologies of revision and recovery, this latest edition includes all new material while still following the format of the original. It is constructed around bibliographical surveys of both primary and secondary works addressing the Classical, Medieval, Renaissance, and more recent periods up to the present. The Present State of Scholarship in the History of Rhetoric doesn't simply update but rather recasts study in the history of rhetoric." "The authors - experienced and well-known scholars in their respective fields redefine existing strands of rhetorical study within the periods, expand the scope of rhetorical engagement, and include additional figures and their works. The globalization and expansion of rhetoric are demonstrated in each part and seen clearly in the inclusion of more female rhetors, discussions of historical and contemporary electronic resources, and examinations of rhetorical practices falling outside the academy and the traditional canon." "New to this edition is a cumulative review of twentieth-century rhetoric along with a thematic index designed to facilitate interdisciplinary or specialized study and scholarly research across the traditional historical periods." "As programs incorporating rhetorical studies continue to expand at the university level, students and researchers are in need of up-to-date bibliographical resources. No other work matches the scope and approach of The Present State of Scholarship in the History of Rhetoric, which carries scholarship on rhetoric into the twenty-first century."--Jacket.